The effect of knee-flexion angle on peak force and muscle activation during isometric knee-flexor strength testing using the Nordbord device in soccer players - Taylor, J. M.; Pallotta, H.; Smith, P.; Short, W.; Wright, M. D.; Chesterton, P. (Science and Medicine in Football, 2026)
Isometric knee-flexor testing is commonplace in soccer, yet data to inform choice of knee-flexion angle are limited. This study aimed to compare peak force production and muscle activation between two isometric knee-flexor tests. To compare peak force, 43 male soccer players (age 21.5 ± 5 years; stature 180.3 ± 6.3 cm; body mass 74.6 ± 8.9 kg) completed 3 × 5-second maximal efforts on the Nordbord device (Vald Performance) with a 0- (ISO-Prone) and 30-degree (ISO-30) knee angle, respectively. To compare peak muscle activation, a further 13 trained male participants (25 ± 6 years; 178.2 ± 5.6 cm; 79.6 ± 13.2 kg) completed 3 × 5-second maximal efforts with wireless surface electromyography electrodes placed on the Gluteus Maximus, Adductor Magnus, Semitendinosus, Biceps Femoris (long and short heads) and Medial Gastrocnemius. Paired samples t-tests were used to detect differences in force output between tests and Pearson`s correlations to quantify associations. A Yuen`s modified t-test estimated the trimmed mean differences in muscle activation between tests. Higher peak forces were observed in the ISO-30, with mean differences of 56.4N (36.8 to 75.9 [95% CI]) and 52.9N (33.7 to 72.3 [95% CI]) for right (367 vs 314N) and left legs (351 vs 294N), respectively. Moderate correlations were observed in peak force for left (r = 0.55 (0.29 to 0.73 [95%CI])) and right (r = 0.64 (0.42 to 0.79 [95%CI]) legs. No differences in muscle activation were observed. Peak force varies between the ISO-Prone and ISO-30, with moderate associations between tests, indicating that the tests should not be used interchangeably.